Clinical and Economic Outcomes in Low-risk Pulmonary Embolism Patients Treated with Rivaroxaban versus Standard of Care - W. Frank Peacock; Craig I. Coleman; Phil Wells; Gregory J. Fermann; Li Wang; Onur Baser; Jeff Schein; Concetta Crivera (Journal of Health Economics and Outcomes Research)
# Background Rivaroxaban, a fixed-dose oral direct factor Xa inhibitor, does not require continuous monitoring and thus reduces the hospital stay and economic burden in low-risk pulmonary embolism (LRPE) patients.